The Genealogical Ethics of Leadership-as-Practice - Joe Raelin (Business Ethics Journal Review, 2020)
Mensch and Barge in their interpretation of Alasdair MacIntyre's critique of genealogical ethics as a basis of ethical weakness in the emerging field of “leadership-as-practice,” suggest that L-A-P is lacking in ethical grounding especially because of its relativist philosophy. I address this valid ethical concern in L-A-P theory by arguing that there is a form of realism in Nietzchean axiology and that the dialogic potentialities in material-social interactions may offer a greater capacity for ethical reflexivity than a reliance on rules.
Keywords: J24; M10; M12; M14; D63; 330; Leadership-as-Practice; Nietzschean ethics; Phenomenology; Critical dialogue